Why smart metrology is no longer optional - Pou, Jean-Michel; Leblond, Laurent (IEEE instrumentation & measurement magazine, 2020)
Smart Metrology is the subject of a work we wrote and published with the Association Française de Normalisation (AFNOR, French Standardization Association) in 2016 [1]. In this new work, we offer a very different vision of the role of metrology in industry from the traditional view, which tends to focus on the management of a stock of measuring instruments. The emergence of Big Data and Artificial Intelligence algorithms has caused us to rethink the role of the metrologist: while the job of auditors has more or less been to stick approval labels on instruments. Big Data, by definition, requires reliable data to produce meaningful results. This article sets out to explain why the metrology we are familiar with has been acceptable until now, and why it has become so important to change our approach so as to concentrate on improving performance and managing resources more efficiently. This article is the translation of the article "Pourquoi la Smart Metrology n'est plus une option" that has been published, in French, in the blog www.smart-metrology.com [2].